Urgensi Pendidikan Seks di Sekolah dalam Upaya Mencegah Bukan Mengajarkan - Mirna Mirna; Sayuna Sayuna; Cut Kumala Sari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The high rate of sexual violence has become a primary concern for the government. Victims of such violence do not distinguish between age or gender; children, both boys and girls, are often among the victims. Sexual education remains a taboo subject in society, as many consider it inappropriate to teach children and lack transparency on the matter. Parents are often reluctant and embarrassed to discuss sexual education with their children.Sex education is an effort to provide knowledge about the function of reproductive organs by instilling moranal, ethical, and religious commitments so that there is no “misuse” of these reproductive organs. Sex education aims to provide comprehensive knowledge and understanding of sexuality including, the function of reproductive organs, reproductive health, prevention of risky behavior, prevention of sexually transmitted diseases, prevention of sexual harassment, and increased understanding of gender identity and sexual orientation. The annual record of the National Commission on Violence Against Women in 2024 noted that sexual violence against women occupied the highest level with a percentage of 26.94%. The high level of sexual violence that occurs is a major concern of the government, victims of violence do not mark age and gender, children are also often victims of both boys and girls. This article uses qualitative methods and literature study methods.